Effect of Activated and Non-activated Carbons on Biogas Production from Municipal Organic Wastes - Bishir Musa; Saleh Alhaji Ado; Rabi'u Abdulgafar; Abubakar Madika; Andrea Kruse (UMYU Journal of Microbiology Research)
Study’s Excerpt